ANALYSIS OF BEHAVIOR CHANGE PROGRAM PARTICIPANTS KRPL ON INCOME FAMILIES - Gustina Siregar; Ainul Mardiyah; Muhammad Anuzul (AGRIUM: Jurnal Ilmu Pertanian, 2016)
The purpose of this study was to determine the effect of changes in the behavior of women farmers MKRPL organic vegetable program participants to earnings of program participants Region Sustainable Food House Model (MKRPL) in the Environment IV. Medan District Urban Village Waterfall Marelan and to investigate the contribution of revenue models Region Sustainable Food House (MKRPL) on household income of women farmers MKRPL program participants in the study area. The method used in sampling is a sampling method that is the total sampling technique used when all members of the population as a sample. Analysis of the data used is qualitative. The results showed that the knowledge, attitudes and skills significantly affect revenues and program participants MKRPL MKRPL programs accounted for 8.52%.